A New Separation, Fractionation and Improving of Abu- Aljeer Asphalt - Abdul-Jaleel, Tariq; Waji Salem, Juma; Mseer Najres, Aws (Anbar Journal of Engineering Sciences, 2016)
The study of springs Abu-Aljeer natural asphalt at proven of al-anbar (Iraq), to find a mean of exploiting the asphalt springs as alternative energy resource, Included two stages The first: Separation the components of asphalt in two ways the first is column chromatography and second represented by extraction- chromatography. The results of separation were 10.20% Asphltene, 89.18% Maltene which separated lately to (Paraffinic 45.23%, Aromatic 28. 39% and Resin 21.66%). The second: Trying to improve the asphalt specifications by using natural materials that are available locally (limestone) with (5, 15, 25, 35%), which have given good results. Rheological properties have been tested, in such average that (virgin Softening was 430C, became 560C, Penetration was 110 dropped 39 and viscosity was 11355 turnedy other 47231cent-Stok, mm2Sec), and flash point ( 1790 C became 200 0C), Fractionated parts of asphalt were characterized by (UV), (FT-IR) spectra. This study also clarified paraffin compounds which represent the main part material and the colloidal state is in Gel phase.